Mindestlohneffekte des Entsendegesetzes? Eine Mikrodatenanalyse für die deutsche Bauwirtschaft - Joachim Möller; Marion König (Zeitschrift für ArbeitsmarktForschung - Journal for Labour Market Research, 2008)
– The aim of this study is to analyze impacts of the introduction of the minimum wage in the German construction sector on wages and employment using micro data. The introduction of the minimum wage in 1997, which is binding for all blue-collar workers, is related to the Worker Posting Law. Following a difference-in-differences approach we propose a method to identify the effects despite the lack of information on working hours. In contrast to other studies the size of the treatment and control group is not exogenously given, but is determined by the maximum-likelihood criterion. Our results show positive wage growth effects of the minimum wage regulation in both the eastern German and the western German construction sector. Regarding the employment effects, the results for the two parts of the country differ clearly. The employment effects are negative for eastern Germany, and positive - although not always statistically significant - for western Germany.
Keywords: 330; Mindestlohn - Auswirkungen; Lohnhöhe; Beschäftigungseffekte; Baugewerbe; Arbeitnehmerentsendegesetz; IAB-Regionalstichprobe; Westdeutschland; Ostdeutschland; Bundesrepublik Deutschland